Cascading spatial and trophic impacts of oak decline on the soil food web. (4th December 2018) - Domínguez‐Begines, Jara; De Deyn, Gerlinde B.; García, Luis V.; Eisenhauer, Nico; Gómez‐Aparicio, Lorena
Abstract: Tree defoliation and mortality have considerably increased world‐wide during the last decades due to global change drivers such as increasing drought or invasive pests and pathogens. However, the effects of this tree decline on soil food webs are poorly understood. In this study, we evaluated the impacts of Quercus suber decline on soil food webs of Mediterranean mixed forests invaded by the exotic oomycete pathogen Phytophthora cinnamomi, using soil nematodes as bioindicator taxa. We used a spatially explicit neighbourhood approach to predict the characteristics of the nematode community (diversity, trophic structure, and several indices indicative of soil food web conditions) as a function of the characteristics of the tree and shrub community (species composition, size, and health status). Our results indicate that the process of defoliation and mortality of Q. suber caused significant alterations in the nematode trophic structure increasing the abundance of lower trophic levels (bacterivores, fungivores, and herbivores) and decreasing the abundance of higher levels (predators and omnivores). Furthermore, Q. suber decline altered the functional composition of soil communities, producing a setback of the ecological succession in the soil food web to an earlier stage (decrease in the maturity index and increase in the plant parasitic index), simplified soil food webs (decrease in the structure index), and shifts in the predominant decomposition channel (increase in the fungivores/bacterivores ratio). We also detected contrasting characteristics of the nematode community in neighbourhoods dominated by coexisting woody species, which suggests potential for long‐term indirect effects on soil food webs due to the substitution of Q. suber by non‐declining species. Synthesis . Our study provides novel results that show the major impacts that ongoing health deterioration of dominant tree species can have on the structure and composition of soil food webs in forest systems invaded by exotic pathogens, with cascading consequences for soil biogeochemical processes in both the short‐ and long term. Abstract : Our study provides novel results that show the major impacts that ongoing health deterioration of dominant tree species can have on the structure and composition of soil food webs in forest systems invaded by exotic pathogens, with cascading consequences for soil biogeochemical processes in both the short‐ and long term.